2002
DOI: 10.1038/sj.onc.1205019
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between phosphotyrosine-mediated signaling properties of conventional and neuronal Shc adapter molecules

Abstract: The phosphotyrosine (pTyr) adapter Shc/ShcA is a major connector in various tyrosine kinase signalings following a variety of stimulation such as growth factor/ neurotrophin, as well as in those following calcium in¯ux and integrin activation. As in other tissues, Shc has been implicated in neuronal signalings; however, recent evidence suggests that N-Shc/ShcC and Sck/ShcB would take over most of the roles of Shc in mature central neurons, and switching phenomena between Shc and NShc expression were observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 49 publications
0
26
1
Order By: Relevance
“…4B), thereby suggesting that, as for the Shc proteins, Y231, Y232, and Y304 are the major Rai tyrosine phosphorylation sites. These results differ from those of a previous report, which showed that NGF treatment induces phosphorylation of overexpressed Rai only at the Y304 site, possibly due to differences in the experimental systems used (GDNF versus NGF and endogenous versus overexpressed Rai proteins) (23). We then measured the ability of a GST-Grb2 recombinant protein to interact with phosphorylated Rai.…”
Section: Rai Does Not Bind Grb2 and Increases Late (Gdnf-induced) Mapcontrasting
confidence: 56%
See 1 more Smart Citation
“…4B), thereby suggesting that, as for the Shc proteins, Y231, Y232, and Y304 are the major Rai tyrosine phosphorylation sites. These results differ from those of a previous report, which showed that NGF treatment induces phosphorylation of overexpressed Rai only at the Y304 site, possibly due to differences in the experimental systems used (GDNF versus NGF and endogenous versus overexpressed Rai proteins) (23). We then measured the ability of a GST-Grb2 recombinant protein to interact with phosphorylated Rai.…”
Section: Rai Does Not Bind Grb2 and Increases Late (Gdnf-induced) Mapcontrasting
confidence: 56%
“…Indeed, preliminary evidences suggest that, like the Shc proteins, Sli and Rai may function as cytoplasmic signaling proteins downstream of activated TK receptors. Both Rai and Sli can bind activated TK receptors, including the EGF receptor (EGFR) and Trk receptor (10,23,24,26). Whether Rai or Sli activates Ras or other intracellular pathways remains to be determined, as do the biological consequences of their activities.…”
mentioning
confidence: 99%
“…The question thus arises as to whether there are any binding partners of Grit in TrkA-negative neurons. To address this issue, we studied the interaction between Grit and (11,33,34,44,50) as well as in many other phosphotyrosine-mediated signalings including the EGF pathway (7,41). By using EGF-treated COS-1 cells overexpressing FLAG-tagged Grit-CT and T7-tagged Shc family members, we found that N-Shc, a central-neuron specific adapter (34), bound efficiently to Grit-CT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Immunoprecipitates were resolved by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and immunoblotted with the desired antibodies. The glutathione S-transferase (GST) pull-down assay was performed as previously described (33). Cell lysates were incubated with 10 to 25 g of GST fusion proteins on glutathione-Sepharose (AmershamPharmacia) for 2 h or overnight at 4°C.…”
mentioning
confidence: 99%
“…As for the difference in the downstream signaling between ShcC and ShcA, little is known so far. Regarding to this point, Nakamura et al (2002) indicated that inhibition of NGF-induced ERK activation by the expression of ShcC was due to the different Grb2-binding capacity between ShcA and ShcC in response to NGF. It was previously reported that ShcA preferentially binds to TrkA (Yamada et al, 2002), which is the key receptor against NGF due to neurite outgrowth with the sustained ERK phosphorylation, ShcC in differentiation of neuroblastoma I Miyake et al whereas ShcC associated with TrkB rather than TrkA (O'Bryan et al, 1998;Liu and Meakin, 2002).…”
Section: Discussionmentioning
confidence: 99%